Polarization demultiplexing by ICA in a polarization multiplexing system with both PMD and PDL - Ling ZHAO; Gui-jun HU; Jin-hua LV; Gong-yu LI; Li LI (Tongxin xuebao)
Due to polarization mode dispersion(PMD)and polarizat dependent loss(PDL)in a system,the coherent detection scheme was chosen at the receiver side of the system and T-CMN algorithm was used to separate the polariza-tion multiplexed signals.Simulation results show that after demultiplexed by independent component analysis(ICA),the transmission quality of polarization signals is obviously improved,and when the optical signal to noise ratio of the sys-tem is greater than 20.86 dB,the bit error rate can be kept lower than10- 9,which meets the requirement of a communica-tion system.